Mengintegrasikan Tri N Ki Hadjar Dewantara - Pirati, Nora; Ramadani , Nia; Djati , Rambu Liarang Kaweda; Resti, Resti; Seuk , Ordiana; Bili , Melkianus; Damani, Johannes Maysan (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
The aim of this activity is to provide training regarding financial management at PT Lapak Karya. Community service was carried out on October 15 2024 at PT Lapak Karya, Jl. Minggiran No.14, RT.51/RW.14, Suryodiningratan, Kec. Mantrijeron, Yogyakarta City, Yogyakarta Special Region. The material presented is relevant to the problems faced by PT Lapak Karya related to financial management. When the activity was carried out it ran smoothly and was welcomed warmly and enthusiastically by the owner of PT Lapak Karya. The owner of PT Lapak Karya hopes that community service activities will be carried out continuously. Community service activities also collaborate with PT lapak which provides material related to financial management of works.